2006
DOI: 10.1007/s00132-006-0966-2
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive approach to implantation of a hip endoprosthesis

Abstract: Early experiences with the two-incision approach at the hip joint are reported. We started in July 2002 and until now 272 procedures have been performed. Blood loss (292 ml) and the need for rehabilitation are reduced, the patients will achieve a Harris Hip Score of more than 90 points within 6 or 8 weeks. Complications related to the approach primarily include irritation of the lateral femoral cutaneous nerve. During the learning curve when the initial shaft model was used, shaft fractures or fissures occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
0
3
0
3
Order By: Relevance
“…B. geringeren Blutverlust, schnellere Schmerzfreiheit oder die Möglichkeit einer schnelleren Rehabilitation [12,32,33]. Einen Literaturüberblick zu Studien der minimal-invasiven Hüftal-loarthroplastik geben Reininga et al [24].…”
Section: Minimal-invasiver Vs Konventioneller Zugangunclassified
“…B. geringeren Blutverlust, schnellere Schmerzfreiheit oder die Möglichkeit einer schnelleren Rehabilitation [12,32,33]. Einen Literaturüberblick zu Studien der minimal-invasiven Hüftal-loarthroplastik geben Reininga et al [24].…”
Section: Minimal-invasiver Vs Konventioneller Zugangunclassified
“…Some authors define an incision length of less than 10 cm as minimally invasive [13][14][15]. Others see the definition in less traumatization of the tissue [16][17][18][19]. The minimally invasive approaches are divided into two groups: "muscle-sparing" and "mini-incision" approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Two-incision MIS has been associated with high complication rates 7,21,22). In this study, periprosthetic fractures were found in 4 (15%) of the first 10 cases.…”
Section: Discussionmentioning
confidence: 59%